Bayesian multilevel modelling of the association between socio-economic status and stunting among under-five-year children in Tanzania - Musheiguza, Edwin; Mbegalo, Tukae; Mbukwa, Justine N. (Journal of Health, Population and Nutrition, 2024)
Article published in the Journal of Health, Population and Nutrition page 42-135